The effects of stretching on running economy – A systematic review with meta-analysis - Maximilian Zechner; Konstantin Warneke; Andreas Konrad (Current Issues in Sport Science (CISS), 2024)
Introduction While all running athletes aim to cover the prescribed distance as fast as possible, the physiological and anatomical profiles of athletes are completely different between the disciplines. While sprint athletes have to exert maximal force in the smallest possible time window, the long-distance runner strives for the most economical movement pattern possible (Barnes & Kilding, 2015). Therefore, defined as oxygen uptake at a velocity at a prescribed percentage of the vVO2max, running economy (RE) has been identified as a decisive performance parameter (Saunders et al., 2004). One identified parameter which moderates RE was Achilles tendon stiffness. While stretching frequently used in warm-ups, it also decreases tissue stiffness. Objective: While some authors recommended the avoidance of stretching prior to running (Wilson et al., 2010), others found no affected economy in response to stretching. To address this research gap, this study was conducted to pool available stretching effects on RE. Methods A systematic search was conducted using MEDLINE/PubMed, Web of Science and Scopus (inception to April, 2024), which was supplemented by a manual search in Google Scholar and reference lists of identified studies. To account for multiple dependent study outcomes, robust variance estimation meta-analysis model was chosen to quantify pooled effect sizes. Controlled acute and chronic studies were included if they were performed in young, healthy participants on RE-parameter (energy/O2-consumption at a prescribed velocities determined at a percentage of VO2max (vVO2). Studies without a control group, patients or without the metabolic parameters were excluded. The PEDro scale and GRADE criteria were applied to evaluate the risk of bias and certainty of evidence, respectively. Results A total of 16 studies were investigated, with 14 studies (6 static stretching, 6 dynamic stretching and 2 static/dynamic stretching) addressing acute effects with 169 participants and 33 effect sizes (ES) matched the inclusion criteria. With a PEDro score of 4.88, study quality was rated fair. Overall, there was a low certainty of evidence without confirming any effect of stretching on RE, with overall group effect of ES = 0.007, −0.15 to 0.17 [95% CI], p = 0.93, τ2 = 0, W2 = 0, static group effect of ES = –0,22, –0,40 to 0,70 [95% CI], p = 0.3, τ2 = 0.18, W2 = 0 and dynamic group effect of ES = –0,07, −0.22 to 0.09 [95% CI], p = 0.35, τ2 = 0, W2 = 0, determined at vVO2 65% - 90%. Discussion Currently, there is no evidence supporting previous recommendations to avoid stretching before running due to reduced RE. However, several methodological limitations, such as high heterogeneity in the velocity used in RE determination, small study sample sizes and comparatively short stretching durations without intensity quantification and a lack of pre-post comparisons bias the certainty of evidence. Accordingly, there is a demand for high quality research that controls underlying mechanisms. References Barnes, K. R., & Kilding, A. E. (2015). Running economy: Measurement, norms, and determining factors. Sports Medicine – Open, 1, Article 8. https://doi.org/10.1186/s40798-015-0007-y Saunders, P., Pyne, D., Telford, R., & Hawley, J. (2004). Factors affecting running economy in trained distance runners. Sports Medicine, 34, 465–485. https://doi.org/10.2165/00007256-200434070-00005 Wilson, J. M., Hornbuckle, L. M., Kim, J.-S., Ugrinowitsch, C., Lee, S.-R., Zourdos, M. C., Sommer, B., & Panton, L. B. (2010). Effects of atatic atretching on wnergy cost and running endurance performance. The Journal of Strength & Conditioning Research, 24(9), 2274-2279. https://doi.org/10.1519/JSC.0b013e3181b22ad6